Preliminary results on the assessment of WirelessHART networks in transient fault scenarios - Ivanovitch Silva (2011)
WirelessHART currently appears as a leading solution for interconnection of wireless devices in industrial process control applications. However, the lack of knowledge about the influence of transient faults in WirelessHART networks can lead to the choice of less reliable topologies. In this work,we propose a simulation model to evaluate WirelessHART networks in the presence of transient faults. We assume that these faults result from noisy environments that disturb communications between devices. The model was developed using the Stochastic Petri Net (SPN) formalism, supported by the Mobius tool. For further developments, we target the development of an application that automates the assessment of a WirelessHART network in transient fault scenarios.